The influence of osh culture and osh climate on the performance of employees in construction projects at PT. X - Sutrisno, Sutrisno; Sembiring, Edison; Sugiarto, Sugiarto (Gema Wiralodra, 2023)
Efforts to prevent work accidents are needed to avoid losses that arise and to improve work safety performance in the workplace, therefore K3 is an effort to get a comfortable workplace and working atmosphere to support the achievement of the highest productivity. This study uses interviews and observations to understand the effect of OSH on employee performance with a saturated sample of 180 respondents and quantifies the survey results in the processing of modified regression analysis. The results of the study show that there is a positive relationship between K3 climate and the performance of Construction Project Employees at PT. X. That is, the better the OSH climate in the work environment, the higher the performance of construction project employees. Furthermore, researchers also found that OSH culture plays a role as a mediator in this relationship. In this context, a positive OHS Culture can have a profound effect on creating a safe, disciplined and safety-oriented work environment.